Abrasion Resistance of Materials - Adamiak, Marcin (IntechOpen, 2012)
Abrasion is the primary type of wear in almost all fields of industry. It is particularly relevant to the longevity of pipelines and pumps and to almost all processing industries and applications where a constant interface exists with abrasive substances such as dust, sediments, or fluids with mineral particles. The performance of systems can be degraded depending on the properties of abrasive particles such as size, velocity, angle of impact and shape. Furthermore, abrasion significantly affects the appearance of end-products, which can be especially important in applications where surface finishes are of prime importance. The use of materials which are resistant to abrasion can help retain the appearance of finished products, cut costs associated with maintenance and wear, and prevent system downtime. Materials which are abrasion-resistant are useful for situations where serious damage and mechanical wear can occur and where there is critical demand. The aim of this book is to evaluate abrasion-resistant materials that are already in use or under development, as well as to present information on new techniques in the design and application of such materials. This book will be of interest to a wide audience of engineers dealing with wear problems.